2020
DOI: 10.1186/s13073-020-00799-2
|View full text |Cite
|
Sign up to set email alerts
|

Single cell characterization of B-lymphoid differentiation and leukemic cell states during chemotherapy in ETV6-RUNX1-positive pediatric leukemia identifies drug-targetable transcription factor activities

Abstract: Background Tight regulatory loops orchestrate commitment to B cell fate within bone marrow. Genetic lesions in this gene regulatory network underlie the emergence of the most common childhood cancer, acute lymphoblastic leukemia (ALL). The initial genetic hits, including the common translocation that fuses ETV6 and RUNX1 genes, lead to arrested cell differentiation. Here, we aimed to characterize transcription factor activities along the B-lineage differentiation trajectory as a reference to ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 125 publications
0
20
2
Order By: Relevance
“…3A and 3B). Of note, SuPERR-seq matched the B-cell subclusters to the different stages of their developmental pathway 33 (Fig. 5).…”
Section: Superr-seq Reveals Greater Heterogeneity Within Major Immune Lineagesmentioning
confidence: 87%
“…3A and 3B). Of note, SuPERR-seq matched the B-cell subclusters to the different stages of their developmental pathway 33 (Fig. 5).…”
Section: Superr-seq Reveals Greater Heterogeneity Within Major Immune Lineagesmentioning
confidence: 87%
“…However, no association with outcome was evident for the IGF2BP3 protein in our population-based biopsy cohort, possibly because of its relatively small size or low number of events. A recent single cell analysis of early therapy response in B-ALL showed that patients with high proliferative features are more sensitive to induction chemotherapy, and that therapy-resistant clones are more likely among the quiescent cell populations [ 37 ]. Hence, IGF2BP3 expression is associated with cell populations that are actively dividing and more are likely to be killed by chemotherapy, which is reflected in the overall outcome of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mehtonen et al used scRNA-seq for investigating cell states and transcription factor activities during normal B-cell differentiation and compared those to leukemic cell profiles of six patients with ETV6/RUNX1 B-ALL at diagnosis and during induction therapy (day 15) [ 58 ]. Their results suggested that ETV6/RUNX1 -positive leukemic cell states are most similar to a pro-B state, differ between patients in cell cycle activity, express genes that reprogram the immune microenvironment, and that the induction therapy may modulate leukemic cells towards a pre-B state.…”
Section: Pathobiology Uncovered By Single-cell Analysismentioning
confidence: 99%
“…However, the clinical significance of these findings needs further clarification, as it is yet unknown whether blasts at various developmental changes or with variable maturation potential have indeed fitness advantage during chemotherapy. In ETV6 - RUNX1 + ALL, scRNA-seq revealed elevated activity of B-lineage differentiation transcription factors (TFs), also including the former leukemia genome-wide association study hit ETS domain-containing protein Elk-3 (ELK3) [ 58 ]. Leukemic TF activities persist during chemotherapy and thus provide potentially exploitable vulnerability option to overcome resistance.…”
Section: High-resolution Cellular Characterization For Future Clinical Managementmentioning
confidence: 99%
See 1 more Smart Citation